Epigenetic silencing BCL6B induced colorectal cancer proliferation and metastasis by inhibiting P53 signaling - Hu, Sui (Am J Cancer Res, 2015)
BCL6B, a homologue of BCL6, has been reported to be frequently methylated in human gastric cancer. The epigenetic change and the function of BCL6B remains to be elucidated in colorectal cancer. 7 colorectal cancer cell lines (RKO, HT-29, DLD1, LOVO, HCT116, SW480, SW620) and 102 cases of primary colorectal cancer samples were used in this study. Semi-quantitative RT-PCR, methylation specific PCR (MSP), Flow cytometry and western blot were employed. Loss of BCL6B expression was found in HT29, RKO LOVO, SW480, SW620 and DLD1 cells, and reduced expression was found in HCT116 cell line. Complete methylation was found in HT29, RKO, LOVO, SW480, SW620 and DLD1 cells, partial methylation was detected in HCT116 cells. Restoration of BCL6B expression was induced by 5-Aza treatment in these colorectal cancer cells. BCL6B was methylated in 79.4% (81/102) of primary human colorectal cancer and reduced expression was associated with promoter region hypermethylation (p < 0.05). Methylation of BCL6B is associated with late stage (p < 0.05) and lymph node metastasis (p < 0.05). Re-expression of BCL6B inhibited cell proliferation, invasion and migration in RKO and HT29 cells. BCL6B activated P53 signaling and induced apoptosis, Re-expression of BCL6B sensitized RKO and HT29 cells to 5-fluorouracil. In conclusion, BCL6B was frequently methylated in human colorectal cancer and its expression was regulated by promoter region methylation. Methylation of BCL6B is a prognostic and chemo-sensitive marker in colorectal cancer. BCL6B suppresses colorectal cancer growth by activating P53 signaling.